Kelangkaan dan Lonjakan Harga Minyak Goreng di Indonesia Dalam Perspektif Ekonomi Islam - Fitriani Saragih; M. Shabri Abd. Majid; Anriza Witi Nasution; Pandapotan Ritonga (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2022)
Since the end of 2021, the Indonesian people have again faced the issue of scarcity and soaring cooking oil prices. The government's efforts to overcome the scarcity of cooking oil production have actually benefited palm oil corporations so that the spike in cooking oil prices will continue until mid-2022 and cooking oil shortages are still being found. This study aims to describe the concept of production, scarcity of production and soaring cooking oil prices in an Islamic economic perspective. To discuss the intended purpose, this study uses the library research method, namely by reviewing the relevant literature both from books, articles and reports. The results showed that the scarcity of cooking oil caused a spike in cooking oil prices in Indonesia. This happens when government policies are not fully in accordance with Islamic economic values. The monopoly activities carried out by palm oil corporations have caused a spike in the price of cooking oil which is very much against the values of goodness. In the view of Islam, the aim of production should be to provide benefit, not hardship to society. Production in the Islamic economy is a collective obligation and the law is fardhu kifayah where producers must produce cooking oil as a basic need in adequate quantities. In Islamic economics, the term scarcity is not known due to limited natural resources, because Allah has guaranteed all human needs on earth. The scarcity of cooking oil that occurs is due to one of them being stockpiled by entrepreneurs or the non-distribution of the cooking oil which has resulted in a spike in the price of cooking oil in Indonesia.